Altered brain networks and connections in chronic heart failure patients complicated with cognitive impairment - Wang, Meixia; Xu, Bo; Hou, Xiaoxia; Shi, Qianru; Zhao, Huimin; Gui, Qian; Wu, Guanhui; Dong, Xiaofeng; Xu, Qinrong; Shen, Mingqiang; Cheng, Qingzhang; Feng, Hongxuan (Frontiers in Aging Neuroscience, 2023)
Objective Accumulating evidence shows that cognitive impairment (CI) in patients with chronic heart failure (CHF) is related to brain network dysfunction. This study investigated brain network structure and rich-club organization in chronic heart failure patients with cognitive impairment based on graph analysis of diffusion tensor imaging data. Methods The brain structure networks of 30 CHF patients without CI and 30 CHF patients with CI were constructed. Using graph theory analysis and rich-club analysis, changes in global and local characteristics of the subjects’ brain network and rich-club organization were quantitatively calculated, and the correlation with cognitive function was analyzed. Results Compared with the CHF patients without CI group, the CHF patients with CI group showed lower global efficiency, local efficiency, clustering coefficient, the small-world attribute, and an increase in the shortest path length. The CHF patients with CI group showed lower nodal degree centrality in the right fusiform gyrus (FFG.R) and nodal efficiency in the left orbital superior frontal gyrus (ORB sup. L), the left orbital inferior frontal gyrus (ORB inf. L), and the right posterior cingulate gyrus (PCG.R) compared with CHF patients without CI group. The CHF patients with CI group showed a smaller fiber number of edges in specific regions. Compared with the CHF patients without CI group, the connection strength of feeder connection and local connection in CHF patients with CI group was significantly reduced, although the rich-club connection strength in CHF patients with CI group was decreased compared with the control group, there was no statistical difference. In addition, the connection strength of rich-club was correlated with the orientation (direction force) of MoCA scale. Conclusion CHF patients with CI exhibited lower global and local brain network properties, reduced white matter fiber connectivity, as well as a decreased strength in feeder and local connections in key brain regions. The disrupted brain network properties and connectivity was correlated with cognitive impairment in CHF patients. These findings suggest that impaired brain network properties and connectivity is an essential feature of progressive structural network disruption, heralding the development of cognitive impairment in patients with chronic heart failure.